Endoscopic Endonasal Access to the Jugular Foramen: Defining the Surgical Approach - Lee, Dennis L.Y.; McCoul, Edward D.; Anand, Vijay K.; Schwartz, Theodore H. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Introduction The endoscopic endonasal approach to the parapharyngeal space (PPS) and jugular foramen is not well defined. We sought to systematically define the important landmarks and limitations of this new surgical technique using an endoscopic transmaxillary transpterygoid corridor.Methods Endoscopic dissection was performed in both sides of two latex-injected cadaver heads. Left-sided dissections were facilitated by the addition of a sublabial maxillary antrostomy. The pterygopalatine fossa, infratemporal fossa, and PPS were sequentially dissected and the endoscopic perspective was examined. Measurements were obtained from the surgical orifices to the upper cervical internal carotid artery (ICA) and internal jugular vein (IJV).Results Successful access to the PPS and jugular foramen was achieved in each dissection. The lateral pterygoid plate, mandibular branch of the trigeminal nerve, middle meningeal artery, levator veli palatini muscle, Eustachian tube, and stylopharyngeal fascia were identified as landmarks for the upper cervical ICA and the IJV. The mean distance from the nasal sill was markedly greater than from an ipsilateral sublabial antrostomy.Conclusion The endoscopic endonasal approach can provide adequate access to the PPS, carotid sheath, and jugular foramen. Multiple landmarks are useful to guide the dissection within these deep spaces and may facilitate the clinical application of this approach.
Keywords: endoscopy; endonasal; infratemporal fossa; parapharyngeal space; jugular foramen; skull base; cranial base; surgery